2011
DOI: 10.1074/jbc.m111.266312
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans and Glucose Prevent Apoptosis in 4-Methylumbelliferone-treated Human Aortic Smooth Muscle Cells

Abstract: Smooth muscle cells (SMCs) have a pivotal role in cardiovascular diseases and are responsible for hyaluronan (HA) deposition in thickening vessel walls. HA regulates SMC proliferation, migration, and inflammation, which accelerates neointima formation. We used the HA synthesis inhibitor 4-methylumbelliferone (4-MU) to reduce HA production in human aortic SMCs and found a significant increase of apoptotic cells. Interestingly, the exogenous addition of HA together with 4-MU reduced apoptosis. A similar anti-apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 48 publications
(50 reference statements)
0
30
1
Order By: Relevance
“…The results showed that exogenous HA had no protective effect upon UVB-induced or serum starvation-induced apoptosis. This contrasts with findings by Vigetti et al (37), in which the addition of exogenous HA was shown to protect human aortic smooth muscle cells from cell death caused by 4-MU treatment; major differences in cell type, culture conditions, and inhibitors used could easily explain the different outcomes.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…The results showed that exogenous HA had no protective effect upon UVB-induced or serum starvation-induced apoptosis. This contrasts with findings by Vigetti et al (37), in which the addition of exogenous HA was shown to protect human aortic smooth muscle cells from cell death caused by 4-MU treatment; major differences in cell type, culture conditions, and inhibitors used could easily explain the different outcomes.…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast, other studies showed that HA treatment induces cell death in cultured human gingival fibroblasts (47) and lymphoma cell lines (48). Thus, the regulatory effect of HA upon cell viability appears to depend upon cell context, even when controlling for the size of HA, because high molecular weight HA has been shown to either promote cellular survival (37) or induce cell death (49) in different cell types.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Certainly, versican cleavage can help loosen the HA strand network, thereby altering the interaction of HA with adhesive proteins and with cell surface receptors. Indeed, a growing body of evidence suggest that HA can also directly participate in sustaining the vitality of several cell types by binding to HA cell surface receptors, mainly to CD44 (72)(73)(74)(75). This molecular interaction seems also to take part in the control of cumulus survival.…”
Section: Discussionmentioning
confidence: 99%